2016
DOI: 10.1002/bse.1917
|View full text |Cite
|
Sign up to set email alerts
|

Fostering Stakeholder Engagement: The Role of Materiality Disclosure in Integrated Reporting

Abstract: This paper studies the determinants of materiality disclosure among International Integrated Reporting Council (IIRC) Pilot Program companies implementing the IIRC Framework. In other words, it studies which variables influence the way in which such companies provides information about their materiality determination process. In order to test our hypotheses we performed a number of statistical analyses on a unique hand‐collected dataset including IIRC and non‐IIRC Pilot Program companies for the 2012 and 2013 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
219
4
7

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 179 publications
(243 citation statements)
references
References 59 publications
13
219
4
7
Order By: Relevance
“…Previous studies focused on materiality predominantly explore the determinants of any disclosures provided about the materiality determination process. For example, some firm-level characteristics strongly orient the disclosure achieved through this process (Fasan and Mio, 2016), similarly to what already demonstrated with reference to the specific IIRC content elements (e.g. Melloni et al, 2016;Stacchezzini et al, 2016).…”
Section: Concept Of Materiality In Corporate Reportingsupporting
confidence: 71%
“…Previous studies focused on materiality predominantly explore the determinants of any disclosures provided about the materiality determination process. For example, some firm-level characteristics strongly orient the disclosure achieved through this process (Fasan and Mio, 2016), similarly to what already demonstrated with reference to the specific IIRC content elements (e.g. Melloni et al, 2016;Stacchezzini et al, 2016).…”
Section: Concept Of Materiality In Corporate Reportingsupporting
confidence: 71%
“…Gerwanski et al () showed how gender diversity increases materiality disclosure quality in the context of integrated reporting, whereas Kilic and Kuzey () found that gender diversity is positively related to forward‐looking disclosures in integrated reporting. Fasan and Mio () have instead found an opposite result whereby the presence of women on a board reduces the materiality disclosure quality. In relation to foreign diversity, Frias‐Aceituno et al (2013a) highlighted the absence of associations between the presence of foreign members on the board and the adoption of integrated reporting, whereas, in relation to age diversity, Alfiero et al () found that older members have a negative effect on decisions to compile an integrated report.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Therefore, some researchers have extended the scope of these studies to integrated reporting. In this regard, some studies have analysed the impact of gender diversity (Alfiero, Cane, Doronzo, & Esposito, ; Fasan & Mio, ; Frias‐Aceituno et al, 2013a; García‐Sánchez & Noguera‐Gámez, ; Gerwanski et al, ; Kilic & Kuzey, ), whereas others examined foreign diversity (Frias‐Aceituno et al, 2013a) and age diversity (Alfiero et al, ). In relation to gender diversity, Frias‐Aceituno et al (2013a) found that the presence of women on the board favours the adoption of integrated reporting.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This different approaches to materiality may be also dependent upon internal characteristics of the organizations (Fasan & Mio, 2017) that are beyond the scope of this article. Monnalisa's reporting process selects the material elements according to relevance for the company and relevance for the stakeholders, whereas that of Dellas proceeds with a survey of the importance and prioritization based on economic, social, and environmental performance influence on stakeholder decisions.…”
Section: Stafer Integrated Report 2017mentioning
confidence: 99%